Multi-element modified nano SiO2 particles, method for constructing efficient CO2 foaming agent and CO2 foaming agent
Through two-step chemical modification of nano-SiO2 particles and compounded with betaine and α-olefin sulfonate, a high-efficiency CO2 foaming agent was constructed, solving the stability of nano-particles in high-temperature and high-salt environments, and significantly improving CO2 The stability and durability of foam meet the needs of deep reservoir migration and foam formation.
Patent Information
- Application Number
- CN202411418806.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
In the prior art, nano SiO2 particles are difficult to maintain stability in high temperature and high salt environments, resulting in poor migration and CO2 foam formation in deep reservoirs, and cannot effectively regulate CO2 gas traversal.
Multivariate modified nano SiO2 particles were prepared by two-step chemical modification, combining γ-glycidyl etheroxypropyltriethoxysilane and dimethyldiethoxysilane, and multivariate modified nano SiO2 particles were prepared and combined with low-concentration beets Combined with alkali and α-olefin sulfonate composite surfactant to build a high-efficiency CO2 foaming agent.
The stability and durability of nano SiO2 particles in high-temperature and high-salt environments have been achieved, which significantly improves the stability and temperature and salt resistance of CO2 foam, and meets the needs of deep reservoir migration and foam formation.
Smart Images

Figure BDA0005080192620000061 
Figure BDA0005080192620000071 
Figure BDA0005080192620000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of enhanced oil recovery, and in particular to a multi-component modified nano-SiO2 particle suitable for medium-high temperature and medium-high salinity oil reservoirs, a method for constructing a high-efficiency CO2 foaming agent, and the CO2 foaming agent. Background Art
[0002] For low permeability reservoirs that are difficult to inject water, gas injection is an effective way to supplement the energy of the formation. Injecting carbon dioxide into low permeability reservoirs can not only effectively improve the recovery rate, but also achieve the goal of underground storage of carbon dioxide. However, due to the heterogeneity of the formation, during the gas injection process, carbon dioxide will penetrate along the fractures or some formations with relatively high permeability but low oil saturation, reducing the formation gas storage rate and weakening the effect of carbon dioxide in improving the recovery rate.
[0003] Foam is an important method to inhibit carbon dioxide gas channeling, and the key lies in the performance of the foaming agent. A good foaming agent has a high foaming rate and forms stable foam. The foam stability can be improved by optimizing the molecular structure of the surfactant, compounding surfactants with different molecular structures, and adding polymers to the foaming agent solution. In recent years, a hot method to improve foam stability is to stabilize the foam with nanoparticles, among which the most used particles are nano-SiO2. The surface of ordinary nano-SiO2 contains a large number of hydroxyl groups, which is highly hydrophilic and not easy to adsorb to the gas-liquid interface. Only after the surface of the particles is modified to make the surface of the particles close to neutral wetting, can such particles form a highly elastic surface film at the gas-liquid interface to show a good foam stabilization effect. At present, two types of modification methods have been developed: one is grafting modification, which forms covalent bonds with a large number of hydroxyl groups on the surface of nano-SiO2 through silane coupling agents such as dimethyldimethoxysilane and dimethyldichlorosilane, thereby bonding some hydrophobic groups to the surface of nanoparticles; for example: CN111171798A, CN112175600A, CN113426367A, etc. By controlling the degree of grafting, the wettability of the particle surface can be controlled. Graft-modified particles can stabilize foam alone or be compounded with other surfactants to stabilize foam. Another modification method is to mix nano-SiO2 particles and surfactants in an aqueous solution, and the surfactants are directional adsorbed on the particle surface through static electricity, hydrogen bonds, etc., so that the wettability of the particle surface changes from hydrophilic to neutral wetting, for example: CN110540833A.
[0004] Neutral wetting nano-silica with greatly improved foam stabilizing properties can be formed by grafting nano-silica with silane coupling agents or by adsorbing surfactants on nano-silica in aqueous solution. However, these nano-particles will quickly precipitate in brine containing calcium and magnesium ions due to the weakened surface hydration. Therefore, these particles are difficult to migrate to deep formations and are unable to generate foam with CO2 in deep formations to regulate CO2 gas channeling. Summary of the invention
[0005] In view of the above-mentioned status of the prior art, especially the problem that the effect of single surfactant in stabilizing CO2 foam is not ideal and nanoparticles are difficult to have both foam stabilization and temperature and salt resistance, the present invention proposes to chemically modify nano-SiO2 particles in two steps so that they have foam stabilization and are temperature and salt resistant. The obtained multi-modified nano-SiO2 particles are compounded with low-concentration betaine and α-olefin sulfonate composite surfactant to construct a high-efficiency CO2 foaming agent.
[0006] Therefore, an object of the present invention is to provide a multi-component modified nano-SiO2 particle and a preparation method thereof. After two-step chemical modification, the obtained nano-SiO2 particle not only has a foam stabilizing effect, but also is temperature and salt resistant.
[0007] The second object of the present invention is to provide a method for constructing a high-efficiency CO2 foaming agent, wherein a high-efficiency CO2 foaming agent can be constructed by compounding multi-modified nano-SiO2 particles with low-concentration betaine and α-olefin sulfonate composite surfactant.
[0008] The third object of the present invention is to provide a CO2 foaming agent system constructed by the above method.
[0009] The technical solution for achieving the above-mentioned invention object can be summarized as follows:
[0010] The invention discloses a multi-component modified nano-SiO2 particle, which is obtained by modifying the nano-SiO2 particle with gamma-glycidyl ether oxypropyl triethoxy silane and dimethyl diethoxy silane.
[0011] According to the present invention, preferably, the particle size of the nano-SiO2 is 10 to 100 nm, and more preferably 10 to 15 nm.
[0012] According to the present invention, preferably, in the multi-modified nano-SiO2 particles, the content of γ-glycidyloxypropyltriethoxysilane is 5 to 15% of the mass of the nano-SiO2 particles, and more preferably 10%;
[0013] According to the present invention, preferably, in the multi-component modified nano-SiO2 particles, the content of dimethyldiethoxysilane is 1 to 3% of the mass of the nano-SiO2 particles, and more preferably 2%.
[0014] According to the present invention, preferably, the water phase wetting angle of the multi-modified nano-SiO2 particles is ≥40°.
[0015] According to the present invention, the method for preparing the above-mentioned multi-component modified nano-SiO2 particles comprises the following steps:
[0016] (1) Step 1 modification: reaction of nano-SiO2 particles with γ-glycidyloxypropyltriethoxysilane
[0017] Disperse nano-SiO2 particles in methanol, add γ-glycidyloxypropyltriethoxysilane, raise the temperature to 50-70°C and react for 8-12 hours;
[0018] (2) Step 2 modification: Reaction of the modified product of step 1 with dimethyldiethoxysilane
[0019] Add dimethyltriethoxysilane to the modified product of step 1 and react at 50-70°C for 8-12h to obtain multi-component modified nano-SiO2 particles.
[0020] According to the present invention, the multi-component modified nano-SiO2 particles are used in a CO2 foaming agent system in the oil reservoir field.
[0021] According to the present invention, a method for constructing a high-efficiency CO2 foaming agent is also provided, which comprises compounding the above-mentioned multi-modified nano-SiO2 particles with a betaine active agent and an α-olefin sulfonate composite surfactant.
[0022] According to the present invention, there is also provided a high-efficiency CO2 foaming agent constructed as above, comprising the following components in percentage by mass:
[0023] 0.1% to 1% multi-component modified nano-SiO2 particles, 0.01% to 0.1% betaine active agent, 0.01% to 0.3% α-olefin sulfonate, and the rest is water.
[0024] According to the present invention, preferably, the amount of the multi-component modified nano-SiO2 particles in the foaming agent is 0.2-0.6% of the mass of the foaming agent.
[0025] According to the present invention, preferably, the α-olefin sulfonate in the foaming agent is C 14-16 The amount of AOS, α-olefin sulfonate, used is 0.05-0.1% of the mass of the foaming agent.
[0026] According to the present invention, preferably, the betaine active agent in the foaming agent is at least one of cocamidopropyl betaine, oleamidopropyl betaine, and erucamidopropyl betaine, and oleamidopropyl betaine is most preferred;
[0027] Preferably, the amount of betaine active agent used is 20-40% of the concentration of α-olefin sulfonate, and more preferably 30-35%.
[0028] The beneficial effects of the present invention are as follows:
[0029] 1. The particles used for foam stabilization must be able to continuously migrate in the formation to adjust the gas mobility in the deep reservoir. The salt content of oilfield water is generally greater than 5×103 mg / L, the poor stability of conventional nanoparticles in oilfield water restricts their practical application in oilfields. The multi-modified nano-SiO2 particles modified in two steps of the present invention can be heated to 80°C and the salt content is 3×10 4 The nanoparticles can be kept stable in water for more than 30 days, which meets the requirements for the migration of nanoparticles to the deep reservoir. However, the stability of unmodified nanoparticles is less than 1 day under the same conditions.
[0030] 2. The present invention has established a method for stabilizing foam by using nanoparticles and surfactants. The CO2 foaming agent is not only stable, but also temperature and salt resistant. The CO2 foaming agent system composed of multi-modified nano-SiO2 particles, betaine active agent, and α-olefin sulfonate can stabilize foam at 80°C, 10MPa, and a salt content of 3×10 4 The half-life of CO2 foam formed under 100 mg / L conditions is more than 9 times higher than that of simple modified nanoparticles and more than 6 times higher than that of simple surfactant α-olefin sulfonate. DETAILED DESCRIPTION
[0031] The invention proposes to prepare heat-resistant and salt-resistant particles with foam stabilizing effect by two-step chemical modification of nano-SiO2 particles, and to construct a high-efficiency CO2 foaming agent with low-concentration betaine and α-olefin sulfonate composite surfactant.
[0032] The multi-component modified nano-SiO2 particles of the present invention are obtained by modifying nano-SiO2 particles with gamma-glycidyloxypropyltriethoxysilane (KH561 coupling agent) and dimethyldiethoxysilane.
[0033] According to the present invention, the above multi-component modified nano-SiO2 particles are obtained by two-step chemical modification, and the preparation method comprises the following steps:
[0034] (1) Step 1 modification: reaction of nano-SiO2 particles with γ-glycidyloxypropyltriethoxysilane
[0035] Disperse nano-SiO2 particles in methanol, add γ-glycidyloxypropyltriethoxysilane (hereinafter referred to as modifier 1), raise the temperature to 50-70°C and react for 8-12h;
[0036] In the first step of the modification process, the γ-glycidyloxypropyltriethoxysilane coupling agent reacts with the hydroxyl groups on the surface of the SiO2 particles to bond to the SiO2 surface. At the same time, the epoxy groups at the ends of the coupling agent molecules gradually open to form vicinal diols. These vicinal diol-containing groups have good water solubility and can prevent Ca in water. 2+ Mg 2+ It reacts with the hydroxyl groups on the surface of SiO2 particles, thereby improving the temperature and salt resistance of the nano-SiO2 particles.
[0037] (2) Step 2 modification: Reaction of the modified product of step 1 with dimethyldiethoxysilane
[0038] Add dimethyltriethoxysilane to the modified product of step 1 and react at 50-70°C for 8-12h to obtain multi-component modified nano-SiO2 particles.
[0039] In order to adjust the water phase wetting angle of the surface of nano-SiO2 particles, dimethyltriethoxysilane (hereinafter referred to as modifier 2) is added to the modified product in step 1 for modification reaction. Dimethyltriethoxysilane can react with the remaining hydroxyl groups on the surface of nano-SiO2 particles and bond to the particle surface, thereby increasing the wetting angle of the particle surface.
[0040] According to the present invention, the particles modified by the above two steps can be distributed on the gas-liquid surface to stabilize the foam. The higher the amount of modifier 1, the better the temperature and salt resistance of the modified nanoparticles. However, if the amount of modifier 1 exceeds 15% of the mass of the nano-SiO2 particles, the residual hydroxyl content on the surface of the nano-SiO2 particles will decrease, which will affect the progress of the grafting reaction in the second step.
[0041] Therefore, in one or more preferred embodiments, in the multi-modified nano-SiO2 particles, the content of γ-glycidyloxypropyltriethoxysilane is 5-15% of the mass of the nano-SiO2 particles, preferably 10%.
[0042] According to the present invention, the higher the amount of modifier 2 added, the more methyl groups are grafted on the surface of the nano-SiO2 particles, and the larger the water phase wetting angle on the surface of the nano-SiO2 particles. However, when the amount of modifier 2 added exceeds 3% of the mass of the nano-SiO2 particles, the stability of the nano-SiO2 particles in salt water will be significantly reduced.
[0043] Therefore, in one or more preferred embodiments, the amount of the modifier 2 added is 1-3% of the mass of the nano-SiO2 particles, preferably 2%.
[0044] In one or more preferred embodiments, the particle size of the nano-SiO2 is 10 to 100 nm, preferably 10 to 15 nm.
[0045] In one or more preferred embodiments, the water phase wetting angle of the multi-modified nano-SiO2 particles is ≥40°.
[0046] A preferred preparation embodiment of the above multi-modified nano-SiO2 particles comprises the following steps:
[0047] (1) Step 1 modification: reaction of nano-SiO2 particles with γ-glycidyloxypropyltriethoxysilane
[0048] Weigh 10 grams of nano-SiO2 particles, add them to a three-necked flask equipped with a stirrer, then add 90 grams of methanol, and stir vigorously for 10 minutes to fully disperse the particles; then take 0.5-1.5 grams of γ-glycidyl ether propyl triethoxysilane, add it to the three-necked flask, stir for 10 minutes, and then heat to 60°C to react for 10 hours;
[0049] (2) Step 2 modification: Reaction of the modified product of step 1 with dimethyldiethoxysilane
[0050] Add 0.1-0.5 g of dimethyltriethoxysilane to the modified product of step 1, and react at 60° C. with stirring for 10 h to obtain multi-component modified nano-SiO2 particles.
[0051] According to the present invention, the multi-component modified nano-SiO2 particles are used in a CO2 foaming agent system in the oil reservoir field.
[0052] According to the present invention, a method for constructing a high-efficiency CO2 foaming agent is also provided, which comprises compounding the above-mentioned multi-modified nano-SiO2 particles with a betaine active agent and an α-olefin sulfonate composite surfactant.
[0053] According to the present invention, there is also provided a high-efficiency CO2 foaming agent constructed as above, comprising the following components in percentage by mass:
[0054] 0.1% to 1% multi-component modified nano-SiO2 particles, 0.01% to 0.1% betaine active agent, 0.01% to 0.3% α-olefin sulfonate, and the rest is water.
[0055] In one or more preferred embodiments, the amount of the multi-component modified nano-SiO2 particles is 0.2-0.6% of the mass of the foaming agent.
[0056] According to the present invention, the α-olefin sulfonate in the foaming agent can be selected from C 14-16 AOS (carbon chain contains 14 to 16 carbons), which is the most common industrial product of α-olefin sulfonate;
[0057] In one or more preferred embodiments, the amount of α-olefin sulfonate used is 0.05-0.1% by mass of the foaming agent.
[0058] In one or more preferred embodiments, the betaine active agent in the foaming agent is at least one of cocamidopropyl betaine, oleamidopropyl betaine, and erucamidopropyl betaine, and oleamidopropyl betaine is most preferred;
[0059] Preferably, the amount of betaine active agent used is 20-40% of the concentration of α-olefin sulfonate, and more preferably 30-35%.
[0060] The technical principles of the present invention are as follows:
[0061] (1) After nano-SiO2 is modified with γ-glycidyloxypropyltriethoxysilane, the groups containing vicinal diols grafted onto the surface of the particles have good water solubility. At the same time, these groups can "bury" the hydroxyl groups on the surface of nano-SiO2 particles, preventing Ca in water from 2+ Mg 2+ The bridging effect on the hydroxyl groups on the surface of SiO2 particles improves the temperature and salt resistance of nano-SiO2 particles.
[0062] (2) The nanoparticles modified in a single step are highly hydrophilic and difficult to distribute to the gas-liquid interface to stabilize the foam; however, after the particles modified in a single step further react with dimethyldiethoxysilane, the water phase wetting angle can be increased to more than 40° and the surface tension can be reduced to less than 55 mN / m. Such particles themselves have a certain foaming ability.
[0063] (3) The betaine surfactant in the composite surfactant can further improve the surface wetting angle of the chemically modified nanoparticles obtained above by "in situ" modification. Generally speaking, the foaming performance of the nanoparticle surface is best when it is close to neutral wetting. In the above chemical modification process, reducing the amount of modifier 1 and increasing the amount of modifier 2 will increase the water phase wetting angle of the obtained nanoparticles, but the hydration ability of the nanoparticles will decrease, and thus the stability in water will decrease. From a practical point of view, the surface wetting ability of the particles can only be changed to a limited extent by adding modifier 2. In order to further improve the foam stabilization ability of the nanoparticles, the betaine surfactant is used to further regulate the wettability of the nanoparticle surface. The betaine surfactant is an amphoteric surfactant with an isoelectric point of pH 6.5, that is, the surfactant behaves as a cationic surfactant when the isoelectric point is less than 6.5. Since the pH value of the saturated CO2 aqueous solution is about 3-4, the betaine surfactant is positively charged under this condition and can be adsorbed on the negatively charged surface of the nano-SiO2 particles, thereby further improving the surface wetting angle of the nanoparticles. This adsorption is a dynamic physical adsorption. Controlling the betaine active agent within a low concentration range will not significantly change the stability of the nanoparticles. (4) The betaine active agent is adsorbed on the surface of the nanoparticles, which can reduce the electrostatic repulsion between the nano-SiO2 particles and the electrostatic repulsion between the nano-SiO2 particles and the α-olefin sulfonate, and promote the above substances to be closely arranged on the gas-liquid surface to form a high-strength interface film. The "multi-faceted" modification of the surface of the nano-SiO2 particles in the present invention, such as chemical modification and physical modification, is the fundamental reason for promoting the adsorption of the nano-SiO2 particles on the gas-liquid surface and closely arranging to form a strong interface film. (5) The synergistic effect of the betaine active agent and the α-olefin sulfonate can reduce the surface tension to below 28mN / m, which is also an important reason for promoting the easy formation and stability of the foam.
[0064] The following is a specific example to illustrate the performance of the modified nano-SiO2 particles, the betaine active agent and the α-olefin sulfonate composite active agent and the foaming agent constructed therefrom.
[0065] The modified nano-SiO2 particles are named NP-xy, wherein "x" represents that the amount of modifier 1 added is x%, and "y" represents that the amount of modifier 2 added is y%.
[0066] The simulated saline used in the evaluation consisted of 2.4×10 4 mg / L NaCl, 0.6×10 4 mg / L CaCl2, with a total salt content of 3×10 4 mg / L. The surface tension was measured by the pull-sheet method in simulated saline at 25°C. The wetting angle was measured by the lying drop method in simulated saline at 25°C after the nanoparticles were centrifuged and pressed into thin slices, with decane as the oil phase. The surface dilation modulus was measured by DSA100 produced by KRUSS in simulated saline at 25°C, with the frequency of the sinusoidal oscillation signal fixed at 0.1 Hz. The thermal stability of the foaming agent was evaluated at a temperature of 80°C and a salt content of 3×10 4 The foam performance was evaluated at 80°C, 8MPa, and 3×10 4 It was carried out under the conditions of mg / L.
[0067] Example 1: Comparison of basic properties of nano-SiO2 particles prepared by adding different amounts of modifier 1
[0068] Nano-SiO2 particles were reacted with 3% to 15% γ-glycidyloxypropyltriethoxysilane to prepare modified nano-SiO2 particles NP-3-0, NP-5-0, NP-10-0 and NP-15-0. The performance of these particles at 80℃ and a salt content of 3×10 4 The stability of the nanoparticles in mg / L water was measured, and parameters such as surface tension and wetting angle were determined. The relevant properties were compared with those of the unmodified nanoparticles NP-0-0. The results are shown in Table 1.
[0069] Table 1 Properties of nano-SiO2 particles modified by different single steps
[0070]
[0071] It can be seen that when the amount of modifier 1 is higher than 10%, the modified particles obtained have good stability in simulated salt water. In addition, by comparing parameters such as surface tension and wetting angle, it is found that the surface properties of the nanoparticles obtained by the first step of modification do not change significantly.
[0072] Example 2: The basic properties of nano-SiO2 particles prepared by fixing the amount of modifier 1 at 10% and comparing the amounts of modifier 2
[0073] The basic properties and application properties of nano-SiO2 particles NP-10-1, NP-10-2, NP-10-3, and NP-10-5 prepared by fixing the amount of modifier 1 γ-glycidyloxypropyltriethoxysilane at 10% were compared with different amounts of modifier 2 dimethyltriethoxysilane. The results are shown in Table 2.
[0074] Table 2 Properties of nano-SiO2 particles modified in different two steps
[0075]
[0076] It can be seen that after the two-step modification of the nanoparticles, the surface tension is significantly reduced and the water phase wetting angle is increased. The higher the amount of modifier 2 dimethyltriethoxysilane, the greater the change in the above parameters, and the better the foam stability of the prepared particles. However, when the amount of modifier 2 is high, the stability of the modified particles becomes worse. In addition, the foaming performance of the simply modified nanoparticles can be analyzed to find that the foaming rate and foam stability are not ideal, which may be related to the high surface tension of the simple particles and the limited increase in the water phase wetting angle of the particle surface.
[0077] Example 3: Comparison of the synergistic effects of betaine active agents and α-olefin sulfonates with different carbon chain lengths
[0078] Alpha-olefin sulfonates with a carbon chain of 14-16 are the longest foaming agents currently. By utilizing the electrostatic attraction between betaine and alpha-olefin sulfonates under weak acid conditions, betaine and alpha-olefin sulfonates can be compounded to improve foaming performance. Table 3 lists the performance of cocamidopropyl betaine LAB, oleamidopropyl betaine OAB, erucamidopropyl betaine EAB compounded with alpha-olefin sulfonate AOS. Considering the solubility and foaming performance of the comprehensive system, it is best to select AOS and OAB compounded in a ratio of 3:1 and 4:1.
[0079] Table 3 Different betaine active agents and α-olefin sulfonates 1) Compound performance
[0080]
[0081]
[0082] Example 4: The amount of modifier 1 is fixed at 10%, and the synergistic foam stabilization effect of the composite system of nano-SiO2 particles and OAB and AOS obtained when the amount of modifier 2 is different is compared.
[0083] Different modified nano-SiO2 particles were compounded with 0.075% AOS and 0.025% OAB to construct foaming agents. The basic properties and application performances of these foaming agents were investigated. The results are shown in Table 4.
[0084] Table 4 Performance of foaming agents composed of different modified particles and 0.075% AOS, 0.025% OAB
[0085]
[0086] It can be seen that the foam stabilization effect of the prepared particles is significantly improved when the dosage of modifier 2 is high. The foam stability of the foaming agent composed of NP-10-2 and the foaming agent composed of NP-10-3 is 6 times higher than that of AOS and more than 9 times higher than that of pure nanoparticles. The performance of the foaming agent composed of NP-10-2 and the foaming agent composed of NP-10-3 is not much different, but it is obvious that the foaming agent composed of NP-10-2 is more economical. From the surface expansion modulus measurement results, it can be seen that the system with good foam stabilization effect has a higher surface expansion modulus, indicating that the nanoparticles and surfactants are adsorbed and arranged on the surface and form a surface film with higher strength.
[0087] Example 5: Comparison of the synergistic foam stabilization effect of NP-10-2 and different surfactants
[0088] In order to analyze the role of surfactants in composite foaming agents, the performance of the system composed of 1% NP-10-2 and different surfactants was compared. The results are shown in Table 5.
[0089] Table 5 Performance of single surfactant and composite surfactant with two-step modified nanoparticles
[0090]
[0091] It can be seen that the foaming performance of the system composed of 1% NP-10-2 and composite surfactant is significantly better than that of the foaming agent composed of 1% NP-10-2 and a single surfactant, among which the foaming agent composed of 1% NP-10-2 and AOS has the same performance as pure AOS, indicating that 1% NP-10-2 and AOS do not produce a synergistic effect, which is related to the fact that both NP-10-2 and AOS are negatively charged and AOS is not easy to adsorb on the surface of nanoparticles. For the composite system of 0.025% NP-10-2 and 0.025% OAB, although OAB will adsorb the surface of nanoparticles and change the wettability of the particle surface under weak acidic conditions, the surface tension of the system is high and the surface expansion modulus is low, so it does not show the best foam stabilization performance.
Claims
1. A multi-component modified nano-SiO2 particle, characterized in that: The multi-component modified nano-SiO2 particles are obtained by modifying nano-SiO2 particles with gamma-glycidyloxypropyltriethoxysilane and dimethyldiethoxysilane.
2. The multi-component modified nano-SiO2 particles according to claim 1, characterized in that: The particle size of the nano-SiO2 is 10-100nm.
3. The multi-component modified nano-SiO2 particles according to claim 1, characterized in that: In the multi-component modified nano-SiO2 particles, the content of γ-glycidyloxypropyltriethoxysilane is 5 to 15% of the mass of the nano-SiO2 particles; Preferably, in the multi-component modified nano-SiO2 particles, the content of dimethyldiethoxysilane is 1 to 3% of the mass of the nano-SiO2 particles.
4. The method for preparing the multi-component modified nano-SiO2 particles according to any one of claims 1 to 3, comprising the following steps: (1) Step 1 modification: reaction of nano-SiO2 particles with γ-glycidyloxypropyltriethoxysilane Disperse nano-SiO2 particles in methanol, add γ-glycidyloxypropyltriethoxysilane, raise the temperature to 50-70°C and react for 8-12 hours; (2) Step 2 modification: Reaction of the modified product of step 1 with dimethyldiethoxysilane Add dimethyltriethoxysilane to the modified product of step 1 and react at 50-70°C for 8-12h to obtain multi-component modified nano-SiO2 particles.
5. The multi-component modified nano-SiO2 particles according to any one of claims 1 to 3 are used in a CO2 foaming agent system in the oil reservoir field.
6. A method for constructing a high-efficiency CO2 foaming agent, which comprises compounding the multi-modified nano-SiO2 particles described in any one of claims 1 to 3 with a betaine active agent and an α-olefin sulfonate.
7. A CO2 foaming agent, comprising the multi-modified nano-SiO2 particles according to any one of claims 1 to 3, comprising the following components in percentage by mass: 0.1% to 1% multi-component modified nano-SiO2 particles, 0.01% to 0.1% betaine active agent, 0.01% to 0.3% α-olefin sulfonate, and the rest is water.
8. The CO2 foaming agent according to claim 7, characterized in that The dosage of the multi-component modified nano-SiO2 particles in the foaming agent is 0.2-0.6% of the mass of the foaming agent.
9. The CO2 foaming agent according to claim 7, characterized in that The α-olefin sulfonate in the foaming agent is C 14-16 The amount of AOS, α-olefin sulfonate, used is 0.05-0.1% of the mass of the foaming agent.
10. The CO2 foaming agent according to claim 7, characterized in that The betaine active agent in the foaming agent is at least one of cocamidopropyl betaine, oleamidopropyl betaine and erucamidopropyl betaine; Preferably, the amount of betaine active agent used is 20-40% of the concentration of α-olefin sulfonate.
Citation Information
Patent Citations
Stable carbon dioxide water-based foam fracturing fluid and preparation method thereof, and application of stable carbon dioxide water-based foam fracturing fluid in improving recovery ratio of shale gas
CN110540833A
Surface cationized silicon dioxide nanoparticles
CN111171798A
Novel foam stabilizer and preparation method thereof
CN112175600A
Method for realizing water-phase foam stabilization through surface modification of nano silicon dioxide
CN113426367A
Method for preparing hydrophobic precipitated silicon dioxide
CN102286220A
Cited By
Oil-resistant anti-freezing corrosion-inhibition foaming agent for gas well as well as preparation method and application thereof
CN121203644A
CO2 foaming agent constructed by surface chemical modified nano-silica particles and low concentration betaine surfactant
CN122978943A